THE USE OF ARTIFICIAL INTELLIGENCE IN GOVERNANCE THROUGH ONLINE MEDIA EVALUATION - Suswanta Suswanta; Linayati Lestari; Wiyono Wiyono; Utami Nur (JURNAL TRIAS POLITIKA, 2023)
As a result of the high value of destructive perceptions of Indonesian government services and the high value of perceptions of corruption in Indonesia, the purpose of this study was to analyse artificial intelligence in Indonesian government governance with the last four-year edition, namely 2018-2022. The research data source reviewed 57 news stories from Indonesian online media. This research data analysis uses the Qualitative Data Software Analysis approach with the NVivo 12 Plus tool and the NCapture feature. The results of the data analysis show that artificial intelligence in Indonesia is seen from four aspects: accountability, transparency, the rule of law, and participation. The results showed that reform and bureaucratic reform from the accountability aspect had the highest percentage, namely 54.55%. Human development and culture from the aspect of participation has a percentage of 33.33%. Ministry of communication and informatics, from law supremacy, has a percentage of 53.85%, and the ministry of health, from the aspect of transparency, has a 21.74%. This study’s findings represent that artificial intelligence systems have efficient and environmentally friendly selling points. However, this research sees that the artificial intelligence system is fundamental and has not been optimised by Indonesian government agencies’ entire scope of work. Even so, it can be seen that the Indonesian government continues to strive for artificial intelligence in the scope of government work so that it is used continuously until people’s satisfaction with the performance of the government system is achieved.